Cross-Sectional Study: Can Cigarette Advertising Influence Health Faculty Students? - Suhat; Yogisutanti, Gurdani (Universitas Airlangga, 2024)
Background: Smoking behavior among faculty students still in a high prevalence. One of the causes of this behavior is the existence of smoking advertisements on various media, including social media. Objective: This research aims to determine smoking behavior among students and their responses to cigarette advertising. Method: This is survey research using a cross-sectional approach. Samples were taken from 69 students who had filled out a questionnaire distributed via Google Forms. Results: The research showed that the average age of respondents was 24 years from 19-44 years. As many as 68.1% were female, and unmarried (63.8%). As many as 26.1% of respondents smoked and the age at which they started smoking was approximately 17 years from the range of 14-19 years with an average of 1-12 cigarettes per day from their pocket money (68%). As many as 29% of respondents were influenced by cigarette advertising, with medium and large levels of influence each at 1.4%. As many as 62.3% of their family members smoke; the majority are fathers (46.4%) and older brothers (8.7%). The results of the research show that smoking behavior is still widely practiced by students at health faculties. Conclusion: Gender and the influence of cigarette advertising related to students' smoking behavior. It’s necessary to invigilate and stop cigarette advertisements in various accessible media. Education for students is needed, and can be included in learning courses, as well as a policy not to smoke in all academic activities, both on and off campus.